Doing Time Wisely: The Social and Personal Benefits of Higher Education in Prison - Baranger, Jillian (The prison journal, 2018)
Much of the research on postsecondary education effects on incarcerated individuals has focused on men. However, given the increased rates of women’s imprisonment over the past 40 years, scholars should examine the impact of higher education in prison on women. In this qualitative study, the authors assess the social and personal benefits of participating in a college behind bars program delivered in a women’s prison. Data gathered with both program participants and faculty suggest that students in the program experienced a reduction in criminogenic attitudes and behaviors as well as positive changes in self-perception.